Att analysera sanningens rörlighet: Objektivitet, politik och fält - Nilsson, Gabriella (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2012)
This article argues that Ethnology has an important research task in studying the changeability of Facts in terms of cultural processes, specifically to pose the questions who, where, how and why in relation to a certain area of knowledge. A fruitful way to do so, the author maintains, would be an analytical approach, combining discourse theory and sociological concepts with inspiration from Laclau and Mouffe, as well as Bourdieu. By exemplifying the theoretical discussion with empirical results from the Thesis Gender power or witch hunt? antagonistic conceptions about men’s violence against women (2009) is highlighted various analytical tools to study the changeability of Truth.